Strategiczny controlling produkcyjny - ograniczenia zastosowania w przedsiębiorstwach przemysłu cementowego - Biadacz, Renata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Intensity, variety and consequences of business environment changes and internal changes in companies influence the management systems, especially strategic management systems. This briefing paper outlines some key concepts of strategic production controlling. The paper contains definition of strategic production controlling and contemplation of beriers of its implementation in cement factories. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 22-30